Application of a novel kind of endoscopic sterile ultrasonic couplant using in miniprobe endoscopic ultrasonography - Yifan Ma; Rui Li; Caifeng Jiang (EngMedicine)
Objective: To investigate the efficacy of a novel endoscopic sterile ultrasonic couplant using miniprobe endoscopic ultrasonography (EUS). Methods: Twelve pigs were randomly assigned to experimental or control groups based on different couplants, with six pigs in each group. The experimental group underwent miniprobe endoscopic ultrasound examination using a sterile ultrasound couplant, whereas the control group underwent examination using purified water. Seven positions were examined: proximal esophagus, distal esophagus, gastric fundus, gastric angle, duodenal bulb, proximal colon, and distal colon. The examination time and imaging qualities of the two groups were compared. Results: The ultrasonic couplant group was superior to the purified water group in terms of examination time, injection volume, image clarity, adjustment frequency, one-time success rate, and number of effective images. The difference between the two groups was statistically significant (p ​< ​0.05). Conclusion: Using a sterile endoscopic ultrasound couplant during miniprobe EUS can shorten the examination time, reduce the medium injection volume, improve the one-time success rate and image clarity, and is worthy of clinical promotion and application.